A Practitioner's Conceptualization of Student Engagement - Alan English (The Advocate, 2024)
Student engagement is one of the most promising concepts in educational research today, as it has been positively correlated to a host of desirable outcomes and negatively correlated to a variety of undesirable outcomes. While there has been tremendous progress in advancing our understanding of student engagement including the developing of student engagement models in recent years, most of that work has been focused on advancing educational research rather than disseminating best practices to P-12 practitioners. The aim here is to provide practitioners a brief coverage on the current literature on student engagement, a concise, practical model of engagement, and its potential practical applications.
Keywords: Student engagement; Self-efficacy; Motivation; Positive feedback loop